A PROPOSED RAPID METHOD FOR MEASURING AREA METHANE EMISSIONS: AN EXPLORATORY APPLICATION IN MANHATTAN, NEW YORK, USA - Payne Jr., Bryce F.; Ackley, Robert; Arend, Mark F. (European Scientific Journal, ESJ, 2015)
Methane is an important greenhouse gas, but methane emissions are poorly understood, in large part due to limited atmospheric methane data on local scales. Local and regional scale methane emissions data are urgently needed to improve modeling of future climate change, and support energy plans and policies to minimize future climate impacts of socio-economically needed energy utilization. There have been numerous recent reports on local ground-level ambient air methane surveys that have provided more thorough data on methane sources in some urban areas. Such surveys generate substantial amounts of high quality ground-level methane concentration data, usually with reliable time and geo-referenced location data. We examined the potential usefulness of such data sets for generation of estimates of methane emissions for surveyed areas. Our efforts focused on development of a generally applicable, relatively simple mass-balance approach to estimate area methane emissions from mobile, ground level ambient air methane concentration and local weather data. The data examined were collected in Manhattan, New York, USA over 5 days in late 2012. Using the ratio of methane emissions (μg m-2s-1) to natural gas usage (μg m-2s-1), the resulting methane emissions estimates for Manhattan were compared to 5 other cities (emissions reported by other investigators using other methods). The emissions estimates for Manhattan derived from ground-level mobile methane surveys were within the range of the estimates for the other cities. In addition, the emissions rates reported for the cities indicate natural gas should not be considered more climate-beneficial than other fossil fuels.